Effectiveness of Sorafenib in Patients with Transcatheter Arterial Chemoembolization (TACE) Refractory and Intermediate-Stage Hepatocellular Carcinoma - Arizumi, Tadaaki (Liver Cancer, 2015)
BACKGROUND AND AIMS: Patients with intermediate-stage hepatocellular carcinoma (HCC) refractory to transcatheter arterial chemoembolization (TACE) are considered to be candidates for sorafenib. The aim of this study was to evaluate the superiority of conversion of treatment to sorafenib on overall survival (OS) for cases refractory to TACE. METHODS: This was a retrospective cohort study carried out on 497 patients with HCC who were treated with TACE therapy at our hospital between January 2008 and December 2013. Fifty-six patients were diagnosed as refractory to TACE during their clinical course and they were divided into two cohorts, (1) those who switched from TACE to sorafenib and (2) those who continued TACE. The overall survival (OS) after the time of being refractory to TACE was evaluated between the two groups. RESULTS: After refractoriness to TACE therapy was confirmed, 24 patients continued with TACE (TACE-group) and 32 patients underwent treatment conversion to sorafenib (sorafenib-group). The median OS was 24.7 months in the sorafenib-group and 13.6 months in the TACE-group (p=0.002). CONCLUSIONS: Conversion to sorafenib significantly improves the OS in patients refractory to TACE therapy with intermediate-stage HCC. Administration of sorafenib is therefore recommended in such circumstances of TACE treatment failure.